Christianity in China : from the eighteenth century to the present - Bays, Daniel H (Stanford, Stanford University Press, 1996)
"This pathbreaking volume forces a reassessment of many common assumptions about the relationship between Christianity and modern China. The overall thrust of the twenty essays is that despite the conflicts and tension that have often characterized relations between Christianity and China, for the past two centuries or more Christianity has been putting down roots within Chinese society, and it is still in the process of doing so. Thus Christianity is here interpreted not just as a Western religion that imposed itself on China, but one that was becoming a Chinese religion, as Buddhism did centuries ago. The essays are organized into four major sections: Christianity's role in Qing society, including local conflicts; ethnicity; women; and the indigenization of the Christian effort. The editor has provided section introductions to highlight the major themes in each section, as well as a general introduction."--Publisher description
Karl Gützlaff's approach to indigenization : the Chinese union / Jessie G. Lutz and R. Ray Lutz -- Contextualizing Protestant publishing in China : the Wenshe, 1924-1928 / Peter Chen-Main Wang -- Growth of independent Christianity in China, 1900-1937 / Daniel H. Bays -- Toward independence : Christianity in China under the Japanese occupation, 1937-1945 / Timothy Brook -- Y.T. Wu : a Christian leader under communism / Gao Wangzhi -- Holy Spirit Taiwan : Pentecostal and charismatic Christianity in the Republic of China / Murray A. Rubinstein
Includes bibliographical references (pages 427-456) and index
Keywords: Christianity -- history; China -- Church history -- 18th century; China -- Church history -- 19th century; China -- Church history -- 20th century; China -- Church history -- 18th century; China -- Church history -- 19th century; China -- Church history -- 20th century; Kirchengeschichte -- 1700-1995; Church history